Study the Impact of Shading on Series-Connected PV Modules - Joseph, E. (Springer Science and Business Media B.V., 2021)
This research paper investigates the consequences of shading by varying the solar irradiances falling on PV modules using MATLAB/ Simulink software. Besides, the effect of different solar irradiances and temperature on PV arrays were also evaluated. Partial shading and full shading are inevitable in a PV system and have a severe impact on the power generation. The shading of the PV modules represents a critical variable in the optimization of solar power generation and energy prediction. Shading has a paramount influence on the current and voltage and could even destroy some or all the cells in the PV module in the event of a hot spot. In this paper, a bypass diode is applied in PV modules to mitigate shading issues. Output power is retained at a higher level when PV modules are connected with bypass diodes. Conversely, environmental conditions such as solar irradiance appear to have a greater impact on short circuit current meanwhile temperature has a prominent effect on voltage open circuit. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.